Development and initial validation of the EDIN scale, a new tool for assessing prolonged pain in preterm infants. Issue 1 (1st July 2001) - Debillon, T; Zupan, V; Ravault, N; Magny, J-F; Dehan, M
Abstract : OBJECTIVE: To develop and validate a scale suitable for use in clinical practice as a tool for assessing prolonged pain in premature infants. METHODS: Pain indicators identified by observation of preterm infants and selected by a panel of experts were used to develop the EDIN scale (Échelle Douleur Inconfort Nouveau-Né, neonatal pain and discomfort scale). A cohort of preterm infants was studied prospectively to determine construct validity, inter-rater reliability, and internal consistency of the scale. RESULTS: The EDIN scale uses five behavioural indicators of prolonged pain: facial activity, body movements, quality of sleep, quality of contact with nurses, and consolability. The validation study included 76 preterm infants with a mean gestational age of 31.5 weeks. Inter-rater reliability was acceptable, with a κ coefficient range of 0.59–0.74. Internal consistency was high: Cronbach's α coefficients calculated after deleting each item ranged from 0.86 to 0.94. To establish construct validity, EDIN scores in two extreme situations (pain and no pain) were compared, and a significant difference was observed. CONCLUSIONS: The validation data suggest that the EDIN is appropriate for assessing prolonged pain in preterm infants. Further studies are warranted to obtain further evidence of construct validity by comparing scores in less extreme situations.